2010
DOI: 10.1001/archoto.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adenoid Surface Biofilm Formation and Chronic Otitis Media With Effusion

Abstract: In pediatric patients, adenoid surface biofilm formation may be associated with COME etiopathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 23 publications
1
47
0
4
Order By: Relevance
“…There is no univerTurkiye Klinikleri J Med Sci 2013;33 (6) sally accepted grading system, but we used a grading system which was used in the previous studies of one of our authors. [7][8][9] Analysis of the data was done using SPSS (SPSS for Windows, version 11.5, SPSS, Chicago, IL). Continuous variables were expressed as mean ± standard deviation (SD) and categorical variables were expressed as percentages.…”
Section: Methodsmentioning
confidence: 99%
“…There is no univerTurkiye Klinikleri J Med Sci 2013;33 (6) sally accepted grading system, but we used a grading system which was used in the previous studies of one of our authors. [7][8][9] Analysis of the data was done using SPSS (SPSS for Windows, version 11.5, SPSS, Chicago, IL). Continuous variables were expressed as mean ± standard deviation (SD) and categorical variables were expressed as percentages.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that 75.4% of children affected by obstructive adenoid hypertrophy (grade 3-4) also presented with chronic rhinitis [31]. Saylam et al [32] pointed out the role of chronic infection of the nose and nasopharynx. Otitis media with effusion has been recently proposed, and adenoid bacterial biofilms seem to play a particularly fundamental role.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Otitis media with effusion (OME) is a multifactorial disease with infection, possibly biofilm in nature (3,4) and Eustachian tube dysfunction (5) are the most widely accepted etiologies. Many risk factors have been associated with this disease: young age (6,7) lack of breast feeding (6,8,9) low mother education, (9)(10)(11) low socioeconomic status (6,10) day care attendance (8,11) parental smoking, (6,11,12) upper respiratory tract infections (6,9,11) allergy (6,9,11,13,14) and snoring.…”
Section: Introductionmentioning
confidence: 99%